Synthesis and Biological Evaluation of Novel 5,7-Dichloro-1,3-benzoxazole Derivatives - N. D. Jayanna; H. M. Vagdevi; J. C. Dharshan; T. R. Prashith Kekuda; B. C. Hanumanthappa; B. C. Gowdarshivannanavar (Journal of Chemistry)
A new class of 5,7-dichloro-1,3-benzoxazole derivatives 4–11 were synthesized by fusing 5,7-dichloro-2-hydrazino-1,3-benzoxazole 3 nucleus with aliphatic acids, active methylene compounds, and with selected esters to form heterocyclic ring systems like 1,2,4-triazoles, pyrazoles, and triazine moieties. The compound 3 on diazotization reaction affords the tetrazole compound. The synthesized compounds were characterized by 1H NMR, IR, Mass, and 13C NMR spectral data and screened for cytotoxic, antimicrobial, antioxidant, and antilipase activities. The compounds 4, 5, and 8 have shown significant antimicrobial activities, whereas compounds 6 and 8 have been emerged as leading cytotoxic agents. The compounds 9, 10, and 11 were found to be strong enzyme inhibitors.